Association between arteriosclerosis index and lumbar bone mineral density in U.S adults: a cross-sectional study from the NHANES 2011–2018 - Xie, Chengxin; Ren, Yu; He, Qiang; Wang, Chenglong; Luo, Hua (Frontiers in Cardiovascular Medicine, 2024)
Background The arteriosclerosis index, defined as the ratio of non-high density lipoprotein cholesterol to high density lipoprotein cholesterol (NHHR), has emerged as a novel biomarker for various diseases. The relationship between NHHR and lumbar bone mineral density (BMD) has not been previously examined. Methods This cross-sectional study analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2011–2018. NHHR was calculated as (total cholesterol—high-density lipoprotein cholesterol)/high-density lipoprotein cholesterol. Lumbar BMD was calculated to Z scores. Weighted multivariate linear regression, subgroup analysis, interaction analysis, generalized additive model, and two-piecewise linear regression were used. Results A total of 8,602 participants were included. The negative association between NHHR and lumbar BMD was consistent and significant (Model 1: β = −0.039, 95% CI: −0.055, −0.023, p < 0.001; Model 2: β = −0.045, 95% CI: −0.062, −0.027, p < 0.001; Model 3: β = −0.042, 95% CI: −0.061, −0.023, p < 0.001). The linear relationship between NHHR and lumbar BMD was significantly influenced by body mass index (p for interaction = 0.012) and hypertension (p for interaction = 0.047). Non-linear associations between NHHR and lumbar BMD Z scores were observed in specific populations, including U-shaped, reverse U-shaped, L-shaped, reverse L-shaped, and U-shaped relationships among menopausal females, underweight participants, those with impaired glucose tolerance, those with diabetes mellitus and those taking anti-hyperlipidemic drugs, respectively. Conclusions NHHR exhibited a negative association with lumbar BMD, but varying across specific populations. These findings suggest that NHHR should be tailored to individual levels to mitigate bone loss through a personalized approach. Individuals at heightened risk of cardiovascular disease should focus on their bone health.